Experimental and numerical investigations on the quasi-static structural properties of fibre metal laminates processed by thermoforming. (15th February 2021) - Fischer, Tobias; Grubenmann, Michael; Harhash, Mohamed; Hua, Wei; Heingärtner, Jörg; Hora, Pavel; Palkowski, Heinz; Ziegmann, Gerhard
Abstract: Recently, increasing development efforts of components made of fibre metal laminates (FMLs), with thermoplastics due to their numerous advantages are remarkable. One-step adhesion and forming approach is an innovative solution to process such laminates reducing the cycle time and delivering failure-free components simultaneously. Hat shaped sections were the chosen geometry in this paper. This process is described considering the temperature, pressure and time progress in addition to the temperature distribution inside the FMLs in different locations. In order to describe the structural behaviour of the hat profiles, top-hat crashboxes were produced and tested via quasi-static three-point bending tests. The investigations were carried out by experimental and finite element simulation. Several parameters are discussed in detail, the top layer (steel and aluminium), the core layer thickness (0.5 and 1.0 mm) and glass fibre orientations (0°/90° and ±45°). The results revealed that by doubling the core thickness, the forming forces and accordingly the absorbed deformation energy were doubled at reduced weight increase. Comparing the experimental and numerical results for the Al-based FMLs, a good agreement regarding the energy absorption deformation mode and the force–displacement progress was reached.